2015
DOI: 10.1186/s12935-015-0274-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of MOTILIPERM on cisplatin induced testicular toxicity in Sprague–Dawley rats

Abstract: Background Cisplatin causes male infertility but the exact mechanism have not been clarified, yet. MOTILIPERM has been implicated in alleviation of infertility in Sprague–Dawley rats caused by cisplatin. We evaluated recovery effect of MOTILIPERM on cisplatin (CIS)-induced testicular toxicity in Sprague–Dawley rats.Methods Five groups were included. The groups are control (CTR), CTR + MOTILIPERM 200 mg/kg/day per oral, CIS 10 mg/kg i.v., CIS 10 mg/kg + MOTILIPERM 100 mg/kg/day, CIS 10 mg/kg + MOTILIPERM 200 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 28 publications
4
35
0
Order By: Relevance
“…Furthermore, the StAR protein level, which was first identified in mid-1980s, has been shown to be important for transferring cholesterol,11,21 from the outer to the inner mitochondrial membrane to synthesize testosterone 22. StAR protein was significantly lower in the CIS-treated groups than in the control group, thus interfering with testosterone production.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, the StAR protein level, which was first identified in mid-1980s, has been shown to be important for transferring cholesterol,11,21 from the outer to the inner mitochondrial membrane to synthesize testosterone 22. StAR protein was significantly lower in the CIS-treated groups than in the control group, thus interfering with testosterone production.…”
Section: Discussionmentioning
confidence: 98%
“…Then, the sections were examined under a light microscope to obtain spermatogenic cell density measurements and renal injury scores. Spermatogenic cell density was determined by measuring the thickness of the germinal cell layer and the diameter of the seminiferous tubules 11. The amount of kidney tubular damage was scored according to the percentage of cortical tubules with epithelial necrosis: 0, normal; 1, ≤10%, 2, 10%–25%, 3, 26%–75%, and 4, ≥75%.…”
Section: Methodsmentioning
confidence: 99%
“…The discrepancy with our results may be linked to the rat strain used, as the Wistar rats in this study had severe reduction in sperm count (to 12% of control). Other studies using Wistar rats have documented >50% reduction in sperm count induced by cisplatin (Hamza, Elwy, & Badawi, ; Heeba, Hamza, & Hassanin, ), while studies using Sprague Dawley rats often report no effect or a relatively modest effect of cisplatin on sperm count (Aksu et al., ; Soni et al., ). Collectively, our findings together with previous studies suggest that Wistar rats may be more suitable than Sprague Dawley rats for modelling the reduction in sperm count induced by cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a single dose of cisplatin induced a substantial weight loss of 8% of body weight by day 5, and 16% by day 10 (compared to 10% weight gain in controls at day 10). This general toxicity of cisplatin in rats is recognised (Ilbey, Ozbek, Cekmen, et al., ; Ilbey, Ozbek, Simsek, et al., ; Soni et al., ), and has been shown to be linearly dependent on cisplatin dose (Soni et al., ). Weight loss, largely due to anorexia, affects 50%–90% of patients receiving cisplatin (Hesketh, ), and is a debilitating problem for patients who are unable to maintain adequate nutrition, contributing to reduced quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in the past indicated that torsion can injure testis and its germ cells (23-25). The spermatic cord torsion is an emergency event that is needed an invasive surgery procedure.…”
Section: Discussionmentioning
confidence: 99%